Work Motivation Factors Affecting Employee Performance at Alang-Alang Lebar Health Center in 2024 - Tri Fani Rahayu; Ririn Noviyanti Putri; Nur Asbon; Medy Purwanto (CV. AFDIFAL MAJU BERKAH, 2025)
Human resources is one of the keys to success in an organization/company. Motivation drives employee performance in completing tasks/challenges in order to achieve organizational/company goals. This study aims to determine the relationship between work motivation (incentives, training, work environment) and employee performance at the Alang-Alang Lebar Health Center in 2024. This study uses a descriptive quantitative research type with a cross-sectional method. This study was conducted on 50 respondents of Alang-Alang Lebar Health Center employees. In proving the effect of incentives, training, and work environment on employee performance analysis, univariate and bivariate analyses were used. The results of this study indicate that there is a relationship between incentives, training, and work environment on employee performance with a p-value < 0.05. The conclusion of this study is that the better the incentives, training, and work environment, the higher the employee performance, so it is hoped that the Alang-Alang Lebar Health Center can continue to improve employee performance in providing services to patients.